A tale of two great mimickers: leprosy or sarcoidosis? A case-based review - Shivraj Padiyar; Reena Kharkele; Ramesh Babu Telugu; S Rima; John Mathew (Indian Journal of Rheumatology)
Leprosy and sarcoidosis are chronic multisystem disorders, with clinical features overlapping with each other. The diagnosis requires a thorough clinical, laboratory, histopathological, and radiological examination. Although it is possible to conclude on one particular diagnosis most of the time, in some cases, even after extensive evaluation, it is difficult to differentiate between the two diseases. In such scenarios, treating both the conditions is warranted. Here, we present a case with a diagnostic dilemma between Hansen's disease and sarcoidosis and systematically discuss the specific pointers which can help to differentiate between the two diseases.